Pengaruh Komunikasi, Kecerdasan Emosional, Dan Kapabilitas Inovasi Individual Terhadap Kinerja Karyawan (Studi Pada Karyawan NK Café Malang) - Ayunani, Sabrina; Mardani, Ronny Malavia; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study is intended to examine and explain the impact of communication, emotional intelligence, and individual innovation capabilities on the performance of NK Cafe Malang employees. A total of 75 respondents were sampled in this research by applying saturated sampling techniques. Quantitative data analysis through multiple linear regression analysis is used as a data analysis method. Data testing was carried out using partial hypothesis testing (t test). The results of the study show that partially (t test) the communication variable has a significant influence on the performance of NK Cafe Malang employees, the emotional intelligence variable also has a significant influence on the performance of NK Cafe Malang employees, and the individual innovation capability variable does not have a significant influence on the performance of NK Cafe company employees. Keywords: Communication, Emotional Intelligence, Individual Innovation Capability and Employee Performance.